2019
DOI: 10.3389/fonc.2019.00502
|View full text |Cite
|
Sign up to set email alerts
|

PVT1 Signaling Is a Mediator of Cancer Progression

Abstract: There is increasing evidence that PVT1 has oncogenic properties and regulates proliferation and growth of many cancers. Themolecular mechanisms of action of PVT1 are mediated, in part, by microRNAs (miRNAs). However, some well-established transcription factors involved in cancer cell proliferation share a common thread of microRNA associations with PVT1. Furthermore, these microRNAs are also involved in mechanisms that lead to the development of drug resistance in cancer cells. While several microRNAs have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…8). PVT1 has been identified to be up-regulated in many tumor tissues and it contributes to the pathophysiology of human cancers [25,26]. In the present study, our results demonstrated that PVT1 was up-regulated in the serum of DN patients and HG-induced MCs, consistent with a previous study [12].…”
Section: Discussionsupporting
confidence: 92%
“…8). PVT1 has been identified to be up-regulated in many tumor tissues and it contributes to the pathophysiology of human cancers [25,26]. In the present study, our results demonstrated that PVT1 was up-regulated in the serum of DN patients and HG-induced MCs, consistent with a previous study [12].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to Myc, PVT1 also activates β-catenin and Cyclin D1 [80]. The interplay between PVT1 and Myc has been intensively studied and reviewed [15].…”
Section: Upregulation Of Myc As a Mechanism Underlying The Gene Desermentioning
confidence: 99%
“…In view of Myc being the most-well-studied oncogene and the 8q24 gene desert as a region that is frequently amplified in cancer, FAM84B stands as a promising target for oncogenic activities; nonetheless, its impact on tumorigenesis remained unknown until recently. As the oncogenic potential of the non-coding RNAs of PVT1 and those within the gene desert ( Figure 1) has been recently reviewed [13][14][15][16][17], we will focus on the emerging role of FAM84B in tumorigenesis in this review. We will briefly discuss the 8q24 gene desert with respect to oncogenesis to set the stage for the following systemic examination of the evidence pertinent to FAM84B-derived tumorigenesis.…”
mentioning
confidence: 99%
“…Plasmacytoma Variant Translocation 1 (PVT1) is a well-known oncogenic lncRNA. PVT1 is found to be be upregulated in several type of human cancers, including bladder cancer, hepatocellular carcinoma, cervical cancer, gastric cancer, lung cancer, prostate cancer and OS [13][14][15]. It has been revealed that PVT1 promotes cancer initiation and progression via acting as competing endogenous RNA (ceRNA) or activating STAT3 signaling or KAT2A acetyltransferase or interacting with MYC [15][16][17].…”
Section: Introductionmentioning
confidence: 99%